Early Detection of Lower Adherence to Long-Term E-Diary Recording: A Checkpoint to Target Early Educational Intervention in Seasonal Allergic Rhinitis - Dramburg, S.; Hernandez Toro, C. J.; Grittner, U.; Tripodi, S.; Arasi, S.; Acar Sahin, A.; Matricardi, P. M. (Wiley, 2026)
Background: Digital symptom monitoring via e-Diary apps can support the diagnosis and management of chronic diseases with trigger-induced exacerbations such as pollen allergies. Attrition is a major challenge for continuous e-Diary usage with an unsupervised approach. Objective: To investigate adherence to e-Diary reporting, its early determinants and predictors in a blended care setting among pollen allergic patients with heterogeneous cultural backgrounds. Methods: The @IT.2020 observational multicenter study recruited patients with diagnosed seasonal allergic rhinitis from seven Southern European/Mediterranean countries. Baseline characteristics were investigated through questionnaires, skin prick tests and serum specific IgE measurements. The study doctors asked patients to record their allergy symptoms via e-Diary (AllergyMonitor, TPS) daily during the clinically relevant season of pollination and increased mould concentrations. Results: Among 815 patients (467 adults, 348 children), the average prescribed e-Diary recording period was 106 (SD 47.1) days, with an average completion rate of 75.2% (SD 21.2%). Children (>= 10 years) filled 73.8% (95% CI 68.1-79.4) of prescribed days without parental support. We identified a stable 'higher' and a more variable 'lower' adherence cluster. Adherence was weakly associated with disease severity, but not with age, gender, country, education or digital literacy. Short-term (first 3 weeks) adherence was strongly associated with long-term adherence (partial R-2 = 0.387, p < 0.001), with 87.6% of lower adherent patients remaining poorly adherent beyond 3 weeks. Conclusion: In a blended care setting, adherence to e-Diary compilation among pollen allergic patients is high, irrespective of age and cultural background. Early identification of lower adherence is possible and might inform early interventions to improve patient adherence.
Keywords: Adherence; Allergic Rhinitis; Allergy Symptoms; Chronic Diseases; E-Diary; Patient Education; Patient-Reported Outcomes; Remote Monitoring; Reporting Behaviour